Dampak belanja irigasi dan jaringan terhadap output PDRB sektor pertanian dan pertumbuhan ekonomi Kota Jambi - Aminah, Siti; Parmadi, Parmadi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to analyze the development of irrigation and network expenditure and the development of GDP output in the agricultural sector of the city of Jambi during the period 2005-2015 and analyze the effect of irrigation and network spending on GDP Output in the agricultural sector and economic growth in Jambi City. The results of the study showed that during the study period of 2005-2015 with an average growth of 61.98%, the average value of GRDP at the price of Jambi City was 157,601.68 in million rupiahs with an average growth of 13.67% and the lowest growth occurred in 2006 at 6.60%. Based on the regression results, the results show that the first model of irrigation and network expenditure has a positive and significant effect on the GRDP of the agricultural sector while in the second model irrigation and network expenditure has no significant effect on economic growth